Analysis of Student’s Arabic Reading Pronunciation Characteristics on Discourse Text - Utami, Sri Nabilah; Nurbayan, Yayan; Maulani, Hikmah (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
Based on the importance of pronunciation in Arabic, this study aims to analyze the pronunciation characteristics of students' reading Arabic texts in the discourse text